KARAKTERISASI FISIKOKIMIA NANOKRISTAL EKSTRAK HERBA SELEDRI ( Apium graveolens L.) DENGAN PERBEDAAN KONSENTRASI POLOXAMER188 - Henni Rosaini; Rina Wahyuni; Boyke Panata Sinaga; Wahyu Margi Sidoretno (JURNAL FARMASI DAN MAKANAN, 2020)
Celery (Apium graveolens L) is a plant of Apiaceae family which contains flavonoids, saponins, tannins, essential oils, apiin, apigenin, choline, asparagine, vitamin A, B, C. Apigenin contained in celery included in the BCS (Biopharmaceutics Classification System) class II, which has low solubility and high permeability drugs. One method for increasing solubility is the nanocrystal method. Where the purpose of this study was to see the effect of differences in the concentration of poloxamer 188 on the characterization of nanocrystal. The results of the particle size analyzer (PSA) showed particle size distribution in formula 1 the concentration of poloxamer 188 40% 6 hour grinding time of 1648.5 nm with a potential zeta value of -11.2. While the formula 2 concentration of poloxamer 188 50% and formula 3 the concentration of poloxamer 188 60% with a 5 hour grinding time of 1049.6 and 1483.2 with a potential zeta value of -12.5 and -8.9. From the FT-IR analysis shows the presence of clusters in formulas 1, 2, and 3 which are not found in apigenin which is a celery marker compound, on the contrary there are groups on apigenin which are not found in formulas 1, 2, and 3.